Pengaruh Kecerdasan Emosional Terhadap Hasil Belajar Siswa Kelas X Pada Mata Pelajaran Ekonomi di SMA Negeri 8 Kota Jambi - Putri, Virginia Natasya; Yudha, Redi Indra (Universitas Batanghari Jambi, 2026)
This study aims to determine the effect of emotional intelligence on the learning outcomes of class X students in economics subjects at SMA Negeri 8 Jambi City. This study design uses quantitative research with a research design using Simple Regression Analysis. The research subjects amounted to 140 students using simple random sampling. The data collection technique used a questionnaire or survey. The data analysis technique is the Normality Test, Homogeneity Test, and Simple Regression Analysis. The results of this study indicate that the coefficient value of B constant = 1.498 states that if the emotional intelligence variable is ignored, then the learning outcomes = 0.099. Based on this, a simple regression equation can be made, namely Y = a + Bx is Y = 1.498 + 0.099X with a value of t count X = 90.488. Thus, the hypothesis that states that there is a significant influence between emotional intelligence on the learning outcomes of class X students in economics subjects at SMA Negeri 8 Jambi City in this study is accepted.